EFFECTIVENESS OF A SELF-MANAGEMENT SUPPORT PROGRAM OF PHYSICAL ACTIVITIES AND SQUARE-STEPPING EXERCISE AMONG OLDER WOMEN WITH A RISK OF KNEE OSTEOARTHRITIS - Suthawas , Rada; Nimit-arnun, Nongpimol; Roojanavech, Sasitorn (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
The purpose of this quasi-experimental research was to examine the effects of a self-management-supporting program using physical activities and square-stepping exercise. The sample was 40 older women with a risk of knee osteoarthritis. They were divided into 2 groups: 20 people in the experimental group and 20 people in the comparison group by simple random sampling with matching age and body mass index. The experimental group received a self-management skill training program focusing on cooperative learning groups, physical activity, and square stepping exercise training for 6 weeks. The data were collected through the severity of disease assessment scale, time up and go test, self-management behaviors, and physical activities. The reliability of the questionnaire evaluated by Cronbach's alpha coefficient was .76. The data were then analyzed by using descriptive statistics, independent t-test, chi-square, and repeated measures ANOVA. The study results revealed as follows: After received self-management skill training program, the experimental group had better mean scores on self-management behaviors (Mexperiment= 81.75, SDexperiment = 4.35; Mcomparison = 53.15, SDcomparison= 8.81; t = 13.01, p = .000) and balancing ability than the comparison group (Mexperiment = 9.00, SDexperiment = 1.37; Mcomparison = 10.97 , SDcomparison = 1.35; t = - 4.56, p = .000). The experimental group also had decreasing mean scores on disease severity than the comparison group (Mexperiment = 10.55, SDexperiment = 6.48; Mcomparison = 77.65 , SDcomparison = 28.55; t = - 10.24, p = .000). The physical activity level between the experimental group and the comparison group was statistically and significantly different after participating in the program (χ2 = .001, p = .000). According to the research results, nurses should implement this program for older adult care to prevent knee osteoarthritis and decrease disease severity.